EFFECTIVENESS OF STARTUP CARDS IN SPARKING BUSINESS IDEAS VIA GAMIFICATION - Risa Santoso; Puji Subekti (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2026)
This study examines the effectiveness of StartUp Cards as a gamification-based learning tool to enhance students’ business ideation abilities. Although gamification has been increasingly applied in entrepreneurship education, empirical evidence on its direct impact on business ideation particularly through structured tools such as StartUp Cards remains very limited. Many students continue to struggle to generate and structure business ideas using conventional methods such as paper-based brainstorming, highlighting the need for interactive and guided media that can systematically support the ideation process. StartUp Cards were introduced to address these limitations by providing structured prompts and multimodal stimuli that help students explore business ideas more effectively. The Paired Sample T-Test results indicated a significant improvement in the experimental group, with pre-test scores (M = 9.00; SD = 0.79) rising to post-test scores (M = 19.24; SD = 0.83), yielding a mean difference of −10.24. The medium effectively created an engaging learning environment and encouraged creativity through its gamified design, which supports divergent thinking. These outcomes are consistent with constructivist learning theory, emphasizing active engagement and experiential learning. Thus, StartUp Cards can be recommended as an effective alternative medium for fostering entrepreneurial skills, especially during the initial stages of business planning.